Social Informatics 6th International Conference, SocInfo 2014, Barcelona, Spain, November 11-13, 2014, Proceedings - Aiello, Luca Maria; McFarland, Daniel (Information Systems and Applications, incl. Internet/Web, and HCI, 2014)
This book constitutes the proceedings of the 6th International Conference on Social Informatics, SocInfo 2014, held in Barcelona, Spain, in November 2014. The 28 full papers and 14 short papers presented in this volume were carefully reviewed and selected from 147 submissions. The papers are organized in topical sections such as network, communities, and crowds; interpersonal links and gender biases; news, credibility, and opinion formation; science and technologies; organizations, society and social good.